Is there a limit to agglomeration? Evidence from productivity of Dutch firms - Marian Rizov; Arie J. Oskam; Paul Walsh (European Regional Science Association (ERSA), 2011)
We compute aggregate productivity of three categories of regions, classified by level of urbanization in the Netherlands, from firm-specific total factor productivity (TFP) measures. TFP measures are estimated by a semi-parametric algorithm, within 2-digit industries, covering agriculture, manufacturing, construction, trade and services, using AMADEUS data over the period 1997-2006. We analyse the productivity differentials across urbanization categories by decomposing them into industry productivity effect and industry composition effect. Our analysis indicates that there is non-linear, inverted U-shape effect of agglomeration on productivity growth but in levels agglomeration is associated with higher productivity.
Keywords: 330